(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines creative activity as an effective form of interactive teaching in Russian language education. The study is based on the ideas reflected in the source conference material and develops them in an English academic format. Particular attention is paid to the shift from teacher-centered transmission of knowledge to dialogic and student-centered learning, in which learners become active participants in communication, interpretation, and co-creation. The article argues that creative practices such as dramatization, project tasks, role performance, festive language events, and structured extracurricular activities intensify motivation, lower psychological barriers, strengthen communicative competence, and broaden students’ cultural horizons. The pedagogical value of creative activity is interpreted not as entertainment added to instruction, but as a meaningful methodological resource that connects language acquisition with personal development, collaboration, and intercultural awareness. The article also outlines the key organizational principles that make such work effective: communicative orientation, the balance of individual, group, and collective forms of participation, aesthetic design of learning events, voluntary involvement, teacher guidance, and systematic planning. It is concluded that creative activity, especially when integrated with classroom and extracurricular work, can significantly enrich the practice of Russian language teaching in higher education.